Amnestus pusillus Uhler, 1876 new to Europe found in Italy (Heteroptera: Cydnidae) - Dioli, Paride; Pascotto, Ernesto; Uliana, Marco (Fragmenta entomologica, 2021)
Specimens of Amnestus pusillus were collected in Veneto, Italy, at light. The species is of American origin and has been recorded previously out of its areal, in Iran and the Asian portion of Turkey. The present record is the first for Europe.